HUBUNGAN JAWA-BALI ABAD X-XI - I Gusti Ayu Surasmi (BRIN, 1994)
This article describes the relationship between Java and Bali in the X-XI CE. It was an interesting period as a timeframe of the marriage between King Udayana as family of the King Warmadewa in Bali and Çri Gunapriyadharmapatni, a descendant of the King Sindok from East Java. This marriage turns out to be an interesting field of study. The following article will try to examine the role of Çri Gunapriyadharmapatni in the ancient Java-Bali relationship. The main sources used in this study are several inscriptions and archaeological remains, especially sources related to Çri Gunapriyadharmapatni.